Frequency of Rh Incompatibility Among Primigravida Women Attending Primary Health Care Centers for Antenatal Care in Basra City: Frekuensi Ketidakcocokan Rh pada Wanita Hamil Pertama Kali yang Mengikuti Pemeriksaan Kehamilan di Pusat Pelayanan Kesehatan Primer di Kota Basra - Amna M. Meshari; Marwa A. Hasan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Fetomaternal Rhesus incompatibility remains a significant clinical concern due to its association with hemolytic disease of the newborn and adverse pregnancy outcomes. Specific Background Understanding the distribution of Rh-negative mothers and incompatible pregnancies in healthcare settings is essential for early detection and management. Knowledge Gap Limited localized epidemiological data restricts the ability to design targeted prevention strategies in tertiary care environments. Aims This study aims to determine the prevalence of fetomaternal Rhesus incompatibility and describe associated blood group distributions among pregnant women in a tertiary hospital. Results The findings indicate a measurable prevalence of Rh incompatibility, with identifiable patterns in ABO and Rh blood group distribution, highlighting potential risk for alloimmunization and neonatal complications. Novelty The study provides updated, context-specific prevalence data that contributes to localized clinical understanding of Rh incompatibility. Implications The results support the importance of routine antenatal screening, timely diagnosis, and appropriate prophylactic interventions to reduce maternal and neonatal risks Keywords: Fetomaternal Incompatibility, Rhesus Factor, Alloimmunization, Pregnancy Screening, Neonatal Risk Key Findings Highlights Detectable proportion of Rh-negative pregnancies indicates ongoing clinical risk Blood group distribution patterns reveal potential exposure to antigen mismatch Screening practices remain essential for early identification and management